The Eurasian Economic Union: Prospective Regional Integration in the Post-Soviet Space or just Geopolitical Project? - Podadera-Rivera, Pablo; Garashchuk, Anna (Centre for European Studies, Alexandru Ioan Cuza University of Iasi, Romania, 2016)
Despite the strong competition on the part of the European Union (EU) to become a main integrator in the Post-Soviet Space, the Russian Federation (RF) has not abandoned the idea of continuing to promote integration among ex Soviet Union’s republics and as a result, on the basis of the Eurasian Economy Community (EAEC), the Eurasian Economic Union (EEU), which is meant to become a link between Europe and Asia, has been created. This contribution aims to analyse the integration in the Post-Soviet Space and the role and perspectives of a new agent in the region, the EEU. With regard to methodology of research, such theoretical methods as analysis of literature and authors’ opinions, analyses of official legal documents and statistics data and comparative analysis of institutions were applied.
https://ejes.uaic.ro/about_EJES.htm#xl_open: Copyright of the articles published in EJES belongs to the author(s). The authors grant EJES the right to publish the article and be recognised as the original publisher. All articles are available under the Creative Commons Attribution License 4.0 which formalises the relation between authors, publisher and third parties.
Keywords: Eurasia - Situación económica; Geopolítica; Eurasian Economic Union; European Union; Integration in PostSoviet Space; Regionalism